Suppression of Cartilage Degradation by Zingerone Involving the p38 and JNK MAPK Signaling Pathway - Jetsada Ruangsuriya (2018)
© Georg Thieme Verlag KG Stuttgart · New York. Zingerone, an active compound that is present in cooked ginger, has been claimed to be a bioactive ingredient that holds the potential of preventing and/or treating diseases involving inflammation. In this study, zingerone was used to discover its properties against joint inflammation using interleukin-1β-induced osteoarthritis in cartilage explant and cell culture models. Zingerone was supplemented into the cartilage explant and cell culture media at different concentrations along with the presence of interleukin-1β, an inducer of osteoarthritis. Markers indicating cartilage degradation, inflammation, and the signaling molecules involved in the inflammatory induction were investigated. Diacerien, an anti-osteoarthritic drug, was used as a positive control. Zingerone at a concentration of 40 μM reduced the level of matrix metalloproteinase-13 to about 31.95 ± 4.33 % compared with the interleukin-1β-treated group and halted cartilage explant degradation as indicated by reducing the accumulative release of sulfated glycosaminoglycans by falling to the control concomitantly with an elevation of the remaining contents of uronic acid and collagen in the explant tissues when zingerone was added. In the SW1353 cell line model, zingerone efficiently suppressed the expression of TNF-α, interleukin-6, and interleukin-8 mRNA levels and tended to reduce the levels of both p38 and c-Jun N-terminal kinase phosphorylation. From the results of this study, it can be concluded that zingerone potentially reduced cartilage degradation, which is partially involved in p38 and c-Jun N-terminal kinases of the mitogen activator protein kinase signaling pathway leading to the reduction of proinflammatory cytokine amplification effects and cartilage-degrading enzyme syntheses. This finding supports the contention that ginger holds positive pharmaceutical effects against osteoarthritis.